In House Training 3S (SDKI. SLKI, SIKI) to Improve Nurses' Knowledge of 3S-Based Nursing Care - Ika Purnamasari; Anisa Ell Raharyani; Yahya Karim (GLOBAL HEALTH SCIENCE GROUP, 2023)
Nurses are obliged to carry out nursing practice in accordance with established standards. The standards set by PPNI (Indonesian Nation Nurses Association) as standards in carrying out nursing care are SDKI (Indonesian Nursing Diagnosis Standards), SLKI (Indonesian Nursing Output Standards), and SIKI (Indonesian Nursing Intervention Standards). In-House Training is one of the efforts to increase nurses' knowledge and skills in conducting 3S-based nursing documentation in accordance with the standards set by PPNI. This training aims to increase nurses' knowledge about 3S-based nursing care. This study is a quantitative study with a pre - posttest design approach without control sample consisting of 131 nurses in a private hospital taken via total sampling. The instrument used was a knowledge questionnaire that had been tested for validity using judgment validity with the result > 0,3 that the all items were valid. Data normality test with Kolmogorov Smirnov with a significance value of 0.000 (abnormal data distribution). Data analysis using Wilcoxon test (sig 0.000). The mean value of the pretest was 43.84 and the mean value of the post test was 89.12. the lowest pretest value was 16 and the highest was 84, while the lowest posttest value (64), the highest posttest (100). A total of 130 nurses (99.23%) experienced an increase in post test scores. There was an increase in nurses' knowledge about 3S-based nursing care before and after training.